Reducing Fumigant Application Rates and Soil Emissions with Plastic Mulch Technology - Joseph W. Noling (EDIS, 2013)
With the new fumigant regulations and rising cost of crop production, including fumigants, it would be desirable to reduce the standard use rate of soil fumigants. The use of higher-barrier, gas-impermeable mulches may make it possible to reduce fumigant application rates by helping to contain the fumigant longer within the soil and reduce overall emissions into the atmosphere. The results of field studies show that fumigant application rates can be reduced by 20 to as much as 40% through the use of virtually impermeable or the more gas-tight TIF mulch films at the time of application. This 5-page fact sheet was written by J. W. Noling and published by the UF Department of Entomology and Nematology, March 2013.